PEMANFAATAN GAYA HIDUP PRIA METROSEKSUAL UNTUK EFEKTIVITAS STRATEGI PERIKLANAN - S, HANI VALENTINA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This paper aims to examine the use of life-style metrosexual man for the effectiveness of advertising strategies. Advertising strategy is a strategy where the company achieve its advertising goals. Advertising strategy consists of two elements that create advertising messages and the selection of appropriate media. Two elements are essential in order to achieve advertising effectiveness. One step in the implementation of the advertising message is showcasing lifestyle. The use of advertisements with the theme of metrosexual men's lifestyle can be used by businesses to market both products and services segment devoted to the man, who initially only to a segment of women only. Businesses can take advantage of famous male celebrities the right to advertising their products and services, which is expected to increase sales.